Democratic Conundrum: Introspecting Complexities and Dynamics in Pakistan's Political Landscape - Souvik Chatterjee (Religion and Policy Journal, 2023)
Research Problem: This research aims to explore the main obstacles hindering Pakistan's democratic transition, including weak economic policies, structural imbalances, and military interference, all of which have led to insecurity, conflict, and the oppression of civilian rule. In addition, this research also aims to understand Pakistan's political culture which combines autocratic and democratic ideologies, as well as how political satisfaction with different regimes impacts the acceptance of military regimes and the inability of marginalized groups to express their opinions under authoritarian rule.